2021
DOI: 10.3390/biom12010048
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer Stem-like Cells Resist Ferroptosis-Induced Cell Death by Active Hsp27-GPX4 Pathway

Abstract: Cancer stem cells (CSCs), a subpopulation of cancer cells responsible for tumor initiation and treatment failure, are more susceptible to ferroptosis-inducing agents than bulk cancer cells. However, regulatory pathways controlling ferroptosis, which can selectively induce CSC death, are not fully understood. Here, we demonstrate that the CSCs of esophageal squamous carcinoma cells enriched by spheroid culture have increased intracellular iron levels and lipid peroxidation, thereby increasing exposure to severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…In this study, we revealed the functional importance of Hspb1 in the proliferation of Tsc2-deficient cells. The mechanistic effect of Hspb1 has been implicated in the regulation of ferroptosis, a mechanism of cell death that is associated with iron metabolism (38,39). In Hspb1-suppressed cells, it is possible that a proliferation suppressive mechanism related to ferroptosis might be induced.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we revealed the functional importance of Hspb1 in the proliferation of Tsc2-deficient cells. The mechanistic effect of Hspb1 has been implicated in the regulation of ferroptosis, a mechanism of cell death that is associated with iron metabolism (38,39). In Hspb1-suppressed cells, it is possible that a proliferation suppressive mechanism related to ferroptosis might be induced.…”
Section: Discussionmentioning
confidence: 99%
“…Some compounds have been identified and validated as SLC7A11 inhibitors, including but not limited to erastin, sulfasalazine, sorafenib, imidazole ketone erastin (IKE) and piperazine erastin (PE) [192,196,209]. For EC, as mentioned above, a recent study found that damage from increased lipid peroxidation can be avoided by upregulating GPX4 and SLC7A11, which rescues ESCC cells from ferroptosis, indicating that targeting SLC7A11 to block this intrinsic protective mechanism against ferroptosis has great potential in the treatment of EC [200]. Undoubtedly, SLC7A11 is a promising target in EC therapy.…”
Section: Targeting Slc7a11mentioning
confidence: 98%
“…compared with normal tissues, GPX4 expression levels are significantly elevated in a variety of tumor tissues, such as triple-negative breast (80), gastric (81) and esophageal (82) cancer, leading to the hypothesis that GPX4 may be an oncogene. It has been shown to be a key regulator of ferroptosis; the overexpression or knockdown of GPX4 can affect the cell lethality of 12 ferroptosis inducers (83).…”
Section: Regulation Of Ferroptosis Through the Gpx4 Pathwaymentioning
confidence: 99%